The role of network sharing in transforming the operator business: Impact on profitability and competition - Bengt G. Mölleryd; Jan Markendahl (International Telecommunications Society (ITS), 2013)
This paper focuses on network sharing on mobile networks and examines the impact on profitability and competition. Network sharing refers to that operators collaborates with its competitors on part of the production of mobile services, and it could vary from passive sharing, like sharing of sites or basic facilities, to active sharing, like radio access networks or even entire networks. The paper takes a global scope on examining the extent of network sharing. The emergence of a sector with dedicated infrastructure or tower companies are documented through a mapping of listed companies' which facilities a detailed financial analysis. The rationale for network sharing could be grouped into three factors: 1) lower cost and reduce capital spending as well as to raise capital, 2) improve coverage and services, and 3) reduce the negative impact on the environment. The increased usage of network sharing throughout the world signals that it is going to develop and in the longer run move focus from infrastructure based to service based competition. Although operators have been able to lower network operation cost the impact on profitability varies. The dedicated tower and infrastructure companies manage considerable higher debt ratios compared to operators potentially having a transformative impact on the operator business. Despite an extensive usage of network sharing - where competitors are collaborating - competition on the retail market prevails. A potential spillover effect from network collaboration to the downstream market is a risk, but the social benefit with larger coverage and improved capacity has so far given extensive support for network sharing.
Keywords: 330; Network sharing; mobile network operators; infrastructure; tower companies; operational and capital expenditures; competition; profitability; financial gearing